"As Far as Possible and as Appropriate": Implementing the Aichi Biodiversity Targets. Issue 6 (22nd September 2016) - Hagerman, Shannon M.; Pelai, Ricardo
Abstract: Past shortfalls to meet global biodiversity targets have simultaneously prompted questions about the relevance of global environmental conventions, and sparked renewed ambition, for example, in the form of the Aichi Biodiversity Targets. While progress toward the Aichi Targets through the Convention on Biological Diversity is well‐documented globally, less is known at the national level. We conducted a systematic content analysis of 154 documents to assess the nature and extent of national implementation of the Aichi Targets using Canada as a case study. Results indicate that most responses are aspirational, with only 28% of responses implemented. Implemented responses tend to be associated with targets with specified levels of ambition that emphasize biophysical values, or targets that are relatively straightforward to achieve in this context (e.g., knowledge capacity and awareness). In contrast, targets focused on equity, rights, or policy reform were associated with fewer actions. Implementation of this latter class of targets is arguably stalled not solely because of a lack of effective target design, but because of lack of fit within existing institutional commitments. This suggests that solutions—in terms of improving implementation—lie not only in overcoming known dilemmas of quantifiability, but also in fostering institutional transformation.